Light Deprivation Induces Depression-Like Behavior and Suppresses Neurogenesis in Diurnal Mongolian Gerbil () - Benson Wui-Man Lau; Chaoran Ren; Jian Yang; Sylvia W. L. Yan; Raymond Chuen-Chung Chang; Mingliang Pu; Kwok-Fai So (Cell Transplantation, 2011)
Recent evidence suggests that adult neurogenesis contributes to the pathophysiology of different psychiatric disorders, including depressive disorder, anxiety disorder, and schizophrenia. Seasonal affective disorder (SAD) is a specific form of recurrent depressive disorder that can be induced by shortened light period. It is unclear yet whether neurogenesis is affected in SAD or under altered light/dark cycle. The present study aims at examining whether neurogenesis and dendritic growth of immature neurons are affected in Mongolian gerbils, a mainly diurnal rodent, under light deprivation. Animals were divided into two groups: the control (kept in 12 h light:12 h dark) and the light-deprived groups (kept in 24 h dark). Depression-like behaviors and neurogenesis were assessed after 2 weeks. Compared with the control group, light-deprived gerbils showed increased immobile time in the tail suspension test and forced swimming test, which indicates induction of depression-like behavior. Cell proliferation in both the hippocampal and subventricular zone were significantly decreased in the light-deprived group, which also showed a decreased neuronal differentiation. Dendritic maturation of immature neurons was suppressed by light deprivation, which is revealed by doublecortin staining and Sholl analysis. The results revealed that the light/dark cycle exerts impacts on neurogenesis and maturation of new neurons. Additionally, the current experiment may offer a model for exploring the relationship among daylight exposure, circadian cycles, depressive behavior, and the underlying mechanisms.